Perceived ease of use and usefulness of big data to audit quality - Revita Chikita Meitasari; Manurung, Elizabeth Tiur (Proceeding International Conference on Accounting and Finance, 2023)
Big data analytics are used extensively in industry 4.0, where technology is becoming more advanced and powerful, but also assists auditors in carrying out audit activities. This means that auditors must better understand how to use big data analytics and become proficient. Therefore, the purpose of this study is to ascertain whether the perceived ease of use and usefulness of big data analytics have an impact on the audit quality of an auditor. The new study’s findings will be compared to those of earlier research to see if there is any consistency. This study’s hypothetico-deductive approach led it to the conclusion that, while perceived usefulness had a statistically significant impact on audit quality, perceived ease of use had no statistically significant impact on audit quality. The organization must enhance the knowledge and expertise of its auditors in order for them to obtain the competencies that are necessary in industry 4.0.